2009
DOI: 10.1063/1.3070544
|View full text |Cite
|
Sign up to set email alerts
|

Pulse generation at 346 GHz using a passively mode locked quantum-dash-based laser at 1.55 μm

Abstract: We report on subpicosecond pulse generation at 346 GHz repetition rate based on InAs/InP quantum dash passively mode locked lasers emitting at 1.55 μm. This is achieved owing to the high optical modal gain of the multilayer InAs/InP quantum dash active region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 9 publications
1
40
0
Order By: Relevance
“…The high modal gain of Qdash lasers, corroborated via lasing from very short cavity lasers, has demonstrated in various reports [5,26,207,244]. In particular, a 120 µm cavity exhibiting lasing with highest exhibited slope efficiency of 0.5 W/A was reported by Merghem et al [245]. The 2×120 µm 2 …”
Section: Inas/ingaasp Materials Systemmentioning
confidence: 82%
See 1 more Smart Citation
“…The high modal gain of Qdash lasers, corroborated via lasing from very short cavity lasers, has demonstrated in various reports [5,26,207,244]. In particular, a 120 µm cavity exhibiting lasing with highest exhibited slope efficiency of 0.5 W/A was reported by Merghem et al [245]. The 2×120 µm 2 …”
Section: Inas/ingaasp Materials Systemmentioning
confidence: 82%
“…42(b). In terms of highest repetition rate, Merghem et al [245] reported a record 346 GHz pulse generation (see Fig. 42(c)) using a passively mode-locked 120 µm long Qdash laser emitting ~560 fs deconvolved pulses with 20 mW peak power and 9 dB extinction ratio.…”
Section: Self-pulsationmentioning
confidence: 99%
“…Due to the broadband gain [5] and fast carrier dynamics [6] of QDs, the resulting lasers are excellent candidates for mode-locking, capable of generating optical pulses with pulse durations down to 312 fs [7] and high repetition rates up to 346 GHz [8]. In order to scale the repetition rate up to the THz range using conventional cavity geometries, the length of the optical cavity must be shrunk to less than 50 μm.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the wide gain bandwidth of certain self-assembled gain materials has enabled sub-picosecond and femtosecond pulsewidths to be obtained [3][4][5]. In parallel, various techniques such as colliding pulse mode-locking (CPML) and harmonic mode-locking have been adapted for diode lasers that allow higher repetition rates to be achieved while avoiding the lower average power associated with short device lengths [1].…”
mentioning
confidence: 99%